A Study to Develop an Instrument to Measure Work Ethic. (April 2015) - Sharma, Baldev R.; Rai, Snigdha
Work ethic is one of the most notable constructs that has endured over a long period of time. Among other things, it indicates the extent to which a person considers work as his central life interest. The purpose of the study on which this article is based is to develop an instrument to measure work ethic. Surprisingly, the role of ethical behaviour has not been adequately studied in India in spite of the widespread clamour in the country against corruption! The instrument to be developed through this study, it is hoped, will enable social and behavioural scientists to study this neglected aspect of employee attitude and behaviour. Data for the study was collected from a sample of 507 managerial employees working in the Indian wing of a multinational organization. The 10-item scale developed through this study is uni-dimensional and its psychometric properties were established with the help of appropriate statistical tools and techniques.